Is necropsy obsolete - An audit of the clinical autopsy over six decades: A study from Indian sub continent - Nikhil Moorchung; Vikram Singh; Ankit Mishra; Seema Patrikar; Sunita Kakkar; Vibha Dutta (Wolters Kluwer Medknow Publications, 2013)
Introduction: Several studies have documented a decrease in the autopsy rate. This study was taken up to analyse the cause of mortality, the discrepancies between the ante mortem and post mortem diagnosis and the discrepancies between diagnoses according to the type of the disease over a period of six decades. Materials and Methods: Autopsy reports and medical records were retrospectively analyzed over a 63 year period from 1947 to 2010. Results: In our study, there was a steady increase in the percentage of neoplastic cases from 1947 to 1994 after which there has been a significant drop. The cases dying due to infection has also shown a steady decline over the years until 1994. After 1994, there has been a significant increase in the deaths until 2010 (p < 0.05). Death due to cardiac causes has shown an increase until 1962 which has been followed by a steady decline. There has been a sudden rise in the number of cases dying due to renal causes between 1994 and 2000 (p < 0.05). There has been a statistically significant decrease in the discrepancies between the ante mortem and the post mortem diagnosis over the years. Discussion: This study shows that therapeutic and preventive measures correctly instituted have significantly reduce the mortality, particularly with reference to cardiac and infectious causes. The discrepancy between antemortem and post-mortem diagnosis in 2010 is still very high at 9.30 percent. The autopsy will continue to remain relevant especially in elucidating the molecular cause of disease.